Attention and multisensory modulation argue against total encapsulation. (2016) - de Haas, Benjamin; Schwarzkopf, Dietrich Samuel; Rees, Geraint
Abstract: Firestone & Scholl (F&S) postulate that vision proceeds without any direct interference from cognition. We argue that this view is extreme and not in line with the available evidence. Specifically, we discuss two well-established counterexamples: Attention directly affects core aspects of visual processing, and multisensory modulations of vision originate on multiple levels, some of which are unlikely to fall "within perception."